THE INFLUENCE OF ADOLESCENT BEHAVIOR ON MENARCHE READINESS IN SMP NEGERI 1 BARUMUN TENGAH PADANG LAWAS DISTRICT - Fatima Siregar (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2022)
The youth group in the world is estimated at 1.2 billion (18%). Female puberty is marked by the arrival of menstruation for the first time (Menarche). Menarche in adolescent girls usually occurs in the age range of 10-16 years. How is the influence of behavior, knowledge, attitudes, and actions of young women towards readiness to face Menarche in SMP Negeri 1 Barumun Tengah. This type of quantitative research with cross sectional approach. The study was conducted at SMP Negeri 1 Barumun Tengah starting from February-April 2020 with a total sample of 56 students. The results of this study can be known that the variable of knowledge influences the readiness of students in facing Menarche with p = 0.001. While the attitude and action variables are not influential on the readiness of students in the face of Menarche. Students with neutral knowledge were not ready to face Menarche by 84.7%. It is expected that students of SMP N 1 Barumun Tengah to improve their behavior regarding the readiness to face menstruation by asking questions such as mothers or midwives so that their behavior will be good in the face of menarce. Teachers are expected to provide counseling guidance to help with menstrual problems so that they are ready to face menstruation more mature and better.